EKSPLORASI ETNOMATEMATIKA PADA RUMAH ADAT KARO SIWALUH JABU DI KABUPATEN KARO - Sinulingga, Annizar; Hasibuan, Eka Khairani; Yahfizham, Yahfizham (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2025)
Learning mathematics in the classroom often makes students bored and tired due to less interesting learning strategies. This study was conducted to minimize these difficulties by using ethnomathematics. Ethnomathematics is a discipline that explores and interprets mathematics within the framework of a cultural context. This study aims to explore the elements of ethnomathematics and find out the symbolic meaning contained in the Karo Siwaluh Jabu traditional house, Karo Regency. This type of research is exploratory research. The data obtained are in the form of descriptive qualitative data with an ethnographic approach, the data sources in this study are primary data obtained directly from the source and secondary data obtained from writings, documents and information that have been previously available and are relevant. Data collection techniques are obtained through observation, interviews, documentation and literature studies related to the Karo Siwaluh Jabu traditional house, Karo Regency. This research was conducted directly at the Karo Siwaluh Jabu traditional house in December 2024 with the results of this study showing that: 1). The mathematical concepts contained in the traditional Karo Siwaluh Jabu house of Karo Regency include: Two-dimensional geometry, namely triangle, square, rectangle, rhombus, trapezoid, circle, hexagon. Three-dimensional geometry, namely cube. The concept of area of flat shapes, volume of spatial shapes, and symmetry 2). The symbolic meaning contained in the traditional Karo Siwaluh Jabu house of Karo Regency contains elements of life that symbolize unity and harmony. 3). The value of mathematical discipline contained in the treatment of measurements, placement of parts of the house, cultural values contained in the construction of the traditional Karo Siwaluh Jabu house, and aesthetic values can be seen in the ornaments and decorative motifs found on the walls of the house.